Prominent Mutation of Intron 22 Inversion in Sporadic Hemophilia: Is It Worth the Antenatal Screening? - Sasanakul W. (2023)
Background: Adequate replacement for patients with hemophilia is costly, especially in countries with limited resources. Objective: Factor VIII gene mutations among Thai patients with hemophilia A were analyzed for the most common mutation. The cost-effectiveness of finding one female without family history of hemophilia possessing the most common factor VIII mutation was compared with the cost of treating one patient with hemophilia. Methods: In all, 109 unrelated patients with hemophilia A, defined as sporadic cases (n=58) and hereditary cases (n=51), were enrolled for genotypic analysis. Results: Intron 22 inversion was prominently found in 34 sporadic (58.6%) and 27 hereditary (51.9%) cases. The screening for intron 22 inversion among females without family history of hemophilia at antenatal care has been optionally suggested. A female with a positive result will undergo further prenatal diagnosis of hemophilia in her male offspring. On the contrary, a female with a negative test result remains at risk to have a hemophiliac son caused by other factor VIII gene mutations not included in the screening but the risk is not as high as intron 22 inversion. Although the screening of factor VIII mutation among females without family history of hemophilia is against the current practice, it has been initiated due to the inadequate treatment provided to patients with hemophilia in countries with limited resources. The study calculated approximately one female with intron 22 inversion would exist among 17,064 females without family history of hemophilia. The cost of screening (194,870 USD) was much less than that of treating one patient with hemophilia from birth to 40 years of age by the current regimen (378,000 USD). Conclusion: Implementing antenatal screening of intron 22 inversion among females without family history of hemophilia is optionally suggested, especially in economically less-developed countries with inadequate treatment service for patients with hemophilia.